Sex-dependent effects of FGF21 on HPA axis regulation and adrenal regeneration after Cushing syndrome in mice - Daniela Díaz-Catalán; Júlia Capó; Arturo Vega-Beyhart; Maria Teresa Rodrigo-Calvo; Mireia Mora; Oscar Vidal; Mattia Squarcia; Joaquim Enseñat; Gregori Casals; Felicia Hanzu (Molecular Metabolism)
Background: Cushing's syndrome (CS) results from prolonged exposure to excessive glucocorticoids (GCs), leading to metabolic disturbances and adrenal insufficiency (AI). Fibroblast growth factor 21 (FGF21) has shown promise as a potential therapeutic target for metabolic disorders. This study explores the effects of FGF21 on adrenal gland function in a mouse model of AI following chronic hypercortisolism and investigates sex-dependent differences in the hypothalamic-pituitary-adrenal (HPA) axis response. Methods: We employed a mouse model of AI after chronic corticosterone (CORT) treatment. The effects of recombinant human FGF21 (hFGF21) administration on adrenal function were evaluated in AI mice. Male and female wild-type (WT) and FGF21-overexpressing transgenic (Tg) mice were subjected to 5 weeks of CORT treatment, reaching CS phenotype, followed by immediate analysis or a 10-week recovery period. Metabolic parameters, HPA axis function, and adrenal gland morphology and gene expression were assessed. Results: Prolonged CORT exposure resulted in metabolic disturbances and HPA axis dysregulation. hFGF21 treatment increased CORT and ACTH secretion in AI mice. FGF21 overexpression influenced glucose homeostasis and insulin regulation during CORT treatment and recovery, with sex-specific effects. Tissue-specific regulation of Klb expression was observed across the HPA axis, with distinct patterns between males and females. Tg mice displayed altered adrenal progenitor cell activation and steroidogenic gene expression. Sex-specific differences were observed in adrenal capsule remodeling and gene expression patterns during recovery. Conclusions: This study reveals the complex interplay between FGF21 signaling and GC-induced metabolic and endocrine changes, suggesting a potential sex-specific role of FGF21 in metabolic regulation and HPA axis recovery following after CS.